Implementasi dan Evaluasi Private Cloud di Laboratorium Komputer - Kuntani, Daniel Wilhenson; Palit, Henry Novianus; Noertjahyana, Agustinus (Jurnal Infra, 2015)
Distributed and parallel applications are growing rapidly in this modern era, and so are the needs for more compute resources. The emerging solution to meet these needs is cloud system. Cloud is a collection of computers working together as a unified system. The cloud system provides compute resources to users.One type of cloud is private cloud. Private cloud has restricted users, who work in the same environment or company. As needed, the deployed cloud service is an Infrastructure as a Service (IaaS), where users can request for certain computer specifications with a specific operating system.Computer laboratories in Petra Christian University have computer resources with sufficient specifications that can be utilized to implement a private cloud. The laboratories are not always used for learning classes, thus their resource usage is not optimal. Therefore, implementation of the private cloud is carried out at one of the computer laboratories.OpenStack cloud framework was used for the implementation. Evaluation was done by measuring the performance of the virtual instances and comparing it to that of the physical hosts. The results were used to further determine the benefits offered by the private cloud.